2019
DOI: 10.31327/chalaza.v4i1.921
|View full text |Cite
|
Sign up to set email alerts
|

Use of Old Coconut Water with Various Skim Concentrations of Milk as a Diluent for Kampong Chicken Semen

Abstract: This study aims to determine the level of skim milk in the best coconut water that can maintain the quality of spermatozoa of native chickens during storage at 5oC. Semen was divided into five tubes (without diluents, diluents with skim milk levels 0%, 6%, 8% and 12, liquid Semen was then stored at 5oC. Observations of motility and viability were carried out at 0, 12, 24 hours, 36, and 48 hours. The results showed that the use of various diluents had a very significant effect (P <0.01) on the motility and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
0
2
Order By: Relevance
“…CE extenders induced better viability than LE and CS (Table 2); this might be due to the CE content having a higher glucose content so that it allows spermatozoa to survive longer. Viability of spermatozoa in previous studies using skim coconut milk 9% in 24-hour storage was 79.90% (Khaeruddin & Srimaharani, 2019) was lower than in this study which was 82.13%, probably due to the presence of glucose content in this study. The viability average at 24-hour storage in the present study was also higher than the report of Danang, Isnaini & Trisunuwati (2012) that found 55.4% in ringer's extender.…”
Section: Sperm Viabilitycontrasting
confidence: 87%
See 1 more Smart Citation
“…CE extenders induced better viability than LE and CS (Table 2); this might be due to the CE content having a higher glucose content so that it allows spermatozoa to survive longer. Viability of spermatozoa in previous studies using skim coconut milk 9% in 24-hour storage was 79.90% (Khaeruddin & Srimaharani, 2019) was lower than in this study which was 82.13%, probably due to the presence of glucose content in this study. The viability average at 24-hour storage in the present study was also higher than the report of Danang, Isnaini & Trisunuwati (2012) that found 55.4% in ringer's extender.…”
Section: Sperm Viabilitycontrasting
confidence: 87%
“…Whereas LE, LS 20 mM glucose, LS 50 mM glucose, CE 20 mM glucose, and CE 50 mM glucose extender were only able to maintain the progressive motility of spermatozoa for up to 48 hours. The spermatozoa motility in 80 mM glucose CS extender was 68.33 ± 5.77% at 48 hours storage, which was higher than previously obtained using coconut water + 9% skim milk extender which was 43.73% in the same type of chicken (Khaeruddin & Srimaharani, 2019).…”
Section: B Effect Of Glucose Concentrationcontrasting
confidence: 63%